Pengujian Ketahanan Kekeringan pada Tanaman Garut (Maranta arundinacea L.) Hasil Mutasi Dengan Radiasi Sinar Gamma - Hidayati, Nuril; Sukamto, Lazarus A.; Juhaeti, Titi (JURNAL BIOLOGI INDONESIA, 2012)
Drought Tolerance Assay on Resulted Mutation of Arrowroot Plant (Maranta arundinacea L.) with Gamma Irradiation. Selection of garut (Maranta arundinacea L.) toward drought stress was conducted in induced mutant by using provenance plants from some semi aridregions of East Jawa. In this research three provenance were used 1) Garut from Dusun Pogal, Desa Lebakrejo, Kec. Purwodadi, Kab. Pasuruan (N1); 2) Garut from Dusun Sembung, Desa Parerejo, Kec. Purwodadi, Kab. Pasuruan (N5); 3) Garut from Dusun Genitri, Desa Gunting, Kec. Sukorejo, Kab. Pasuruan (N8). Provenance plants were treated with mutation induction using several levels of gamma radiation i.e. 0, 10, 20 and 40 Gy. The inducted plants were thenplanted in optimum environmental condition for acclimatization. After 5 months the plants were placed in a greenhouse for water stress treatments. Three levels of water regimes 1) optimum water (field capacity Ã = -0,3 to -1,5 Mpa); 2) 7 days watering interval (Ã =-1,0 to -11,0 Mpa); 3) 14 days interval (Ã = -4,0 to -15,0 Mpa). Plant drought tolerance was examined by analyzing morphological and physiological characteristics related to drought tolerant characteristics, including stomatal conductance (stomatal opening), transpiration, rate of CO2 assimilation, biomass production and yield, Harvest Index and drought Tolerance Index. The resultsshowed that radiation treated plants were more capable of maintaining their water potential (Ã). This indicated by significantly higher values of Ã in treated plants i.e. -2.95 Mpa(10 Gy),-2.86 Mpa (20 Gy) and -2.84 Mpa (40 Gy), compared to -3.74 (Untreated plants). Drought stressed plants produced total biomass 79,55 g/plant, much lower compared to unstressed plants (308,20 g/plant). The highest yield was N8 (219,53 g biomass and 139,83 g tuber), followed by N1 (183,32 g biomass and 126,20 g tuber) and N5 (178,8 g biomass and 136,64 g tuber). Drought Tolerance Index of untreated N1 was the highest (1,27), followed by N5 treatedwith 40 Gy (1.22), N1 with 10 Gy (1.17) and N8 with 40 Gy (1.00). Among radiation treatments, untreated plant produced the highest yield followed by the plants treated with 10 Gy, and the lowest was treated with 40 Gy.Keywords: Drought, tolerance, Maranta arundinacea, mutation, gamma, radiation